Strength of Onyx-based composite 3D printing materials according to fiber reinforcement - Lee, Gyu-Wol; Kim, Tae-Hyun; Yun, Jong-Hwan; Kim, Nam-Joo; Ahn, Ki-Hwan; Kang, Min-Soo (Frontiers in Materials, 2023)
This study aims to evaluate the mechanical strength of 3D printed objects of composite material. The composite material considered in this study comprises onyx as the basic material, and glass fiber and carbon fiber as the internal reinforcements. 3D printing using composite materials generally involves laminating fiber reinforcements in the form of layers within the printed part. To analyze the effect of such reinforcements on the printed parts, specimens are prepared by varying the number of layers and arrangement conditions of the reinforcement. The analysis shows that the tensile strength increases with the number of reinforcement layers. Furthermore, a higher tensile strength is observed when the reinforcements were laminated at regular intervals than when they are arranged in the center.